Analysis of the thermal processing influence on the microstructure of a metal-ceramic 3D part created by the additive technilogy method; Междисциплинарные проблемы аддитивных технологий - Fomin V. M.; Golyshev A. A.; Malikov А. G.; Orishich A. M.; Filippov A. A.; Ryashin N. S. (2017, 2017)
Заглавие с титульного экрана